SIGNIFICANCE OF USING UPAMANA PRAMANA IN AYURVEDA (International Journal of Ayurveda and Pharma Research, 2016)
Ayurveda, the ancient Medico Holistic Science, which is comprised of numerous fundamental concepts with basic doctrines. Ayurveda along with its concepts is eternal (Shaswata), and have their own identity which does not require other science to indulge in between. Such fundamental concepts are literally better understood, analyzed and merely utilized in clinical practice only with the proper utility of Pramanas. Pramanas in Ayurveda are means of true knowledge. Acharya Sushruta describe four Pramanas and among the four Pramanas i.e. Pratyaksha (Direct perception), Agama (Teaching of scriptures), Anumama (Inference), Upamana (Analogy). Upamana Pramana is used widely in Ayurvedic literatures. Upamana is having its own importance. Upamana or Aupamya give the knowledge or idea of an object by similar comparison. Acharya Charaka has not included Upamana Pramana under Pramanas but he described it under Vada Marga i.e. technical terms used in Sambasha by Vaidya-Samuha and ultimately helps in attaining valid knowledge, but more than being used in Sambasha, Upamana is having its clinical utility. Upamanas are the analogies or similes that bridge the known to the unknown and after the conceptual system of existing knowledge by modifying and strengthening its associations. Prime intention of such Upamana is incorporating open-ended, forced and visual similes to teach complex concepts and involving students in a creative dynamic though process to enhance understanding of such complex medical concepts. But we have to be very careful about its understanding such analogies, otherwise it may lead to wrong concepts. As said that â€œAn Analogy is like a car, if you take it too far, it breaks downâ€. So here a sincere effort has been made to evaluate and analyze the Upamana Pramana in a simple way in three aspects i.e., physiological, diagnostic, philosophical aspects.